At work but earning less: trends in decent pay and minimum wages for young people - Grimshaw, Damian (Geneva, 2015)
"The paper “At work but earning less: Trends in decent pay and minimum wages for young people” reviews existing literature and analyses recent data on young workers’ earnings. The findings of the paper point to the increase over time of the youth wage discount, i.e. the wage gap between adult and young workers."